Diverting the Gila the Pima Indians and the Florence-Casa Grande Project, 1916-1928 - DeJong, David H. (University of Arizona Press, 2021)
"Diverting the Gila explores the complex web of tension, distrust, and political maneuvering to divide and divert the scarce waters of Arizona's Gila River among residents of Florence, Casa Grande, and the Pima Indians in the early part of the twentieth century. It is the sequel to David H. DeJong's 2009 Stealing the Gila, and it continues to tell the story of the forerunner to the San Carlos Irrigation Project and the Gila River Indian Community's struggle to regain access to their water."--